A case of chronic neuropathic pain treated with auricula injection of local anaesthetic - Paolo Barbagli; Francesco Ceccherelli (Publiediting, 2006)
The case under discussion is that of a 69 years old woman, who has suffered from saphenus nerve neuralgia for about one and a half years. This illness has proved resistant to all the therapeutic treatments she has undergone. The case has been solved in just one session of a rarely used technique, not even well-documented in literature: the injection of local anaesthetic into some auricular points. After about one month of significant aggravation, the pain has disappeared and it has never reappeared throughout the 1-year follow up. The new denomination suggested for this technique is neural-auriculotherapy, which well summarizes the therapeutic branches from which it stems.